Environmental impact on residents’ well-being in the vicinity of quarrying - Wan Hasmirah Wan Ibrahim; Emma Marinies Ahmad Zawawi; Julitta Yunus; Nurfashiha Hashim; Khalida Mohd Sukur (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigates the quality of life of the large population living in the vicinity of quarrying. The negative impact of quarrying activities, such as health problems and air pollution is among the variables that influence human well-being. The objective of this study is to investigate the residents’ experience of air quality in their area and to provide suitable preventive measures to reduce air pollution. A set of questionnaires was distributed to the community at Bandar Saujana Putra and Taman Kajang Perdana, in Selangor. Residents were randomly selected to participate in this study. The study reveals that the community was concerned about health conditions and safety. It is anticipated that this study could assist both residents and authorities in improving the quality of air in this area by providing suitable preventive measures to reduce the environmental impact.